Analisis Remunerasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Dalam Pengawasan Rokok Ilegal (Studi Pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean B Sidoarjo) - Moch Rifai (Universitas Islam Kadiri, 2023)
This study aims to analyze the remuneration and work discipline of employees' performance in controlling illegal cigarettes (a study at the Customs and Excise Office of Customs and Excise Control and Exice Type Sidoarjo) partially and simultaneously. Data was obtained by distributing questionnaires to employees of KPPBC TMP B Sidoarjo. data analysis using multiple regression analysis. The results of this study indicate that there is a simultaneous influence on the variables (remuneration and work discipline) on employee performance with a significance value below 0,05, namely 0,000 < 0,05. work discipline has significant effect on employee performance with a significant value below 0,05, namely 0,003 < 0,05. in the determination test there is an effect of 60,7% of the independent variable on the dependent variable. while 39,3% are influenced by other variables and are not included in this regression analysis, such as job satisfaction, leadership style, training and others.